Experiment on hydrogen from water through catalyst and ultra-violet light - Yeo, Wei Ann. (2009)
The main source of energy for the modern world is crude oil. However, the supply of crude oil is limited. Thus, various new energy sources have been developed to replace our dependency on crude oil and one of the sources of energy is hydrogen. The aim of this project is to study the effect of the photocatalyst on water to observe if hydrogen gas can be produced under ultra violet radiation without the used of electricity to spilt the water molecule. Also study the effect of adding Co catalyst and additive which have different mechanisms of approached to dissociate water to hydrogen hoping to increase the yield. Materials such as zinc nickel and copper are selected base on the various mechanisms proposed and study. But the main objective of this project is to successful conduct test to spilt water into hydrogen under ultra violet radiation.